From ground zero of the pandemic – nurses’ stories via Photovoice - Çetin, İbrahim; Türkben Polat, Hilal; Burucu, Rukiye; Cantekin, Işın (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. With the ongoing COVID-19 pandemic, healthcare workers continue to work selflessly and intensively despite many occupational hazards. Although various studies have been carried out to evaluate the experiences of nurses who play an important role in the fight against the pandemic and the effects thereof, qualitative studies carried out using the photovoice technique are very limited. The aim of this study was to evaluate the experiences of nurses working during the COVID-19 pandemic and show the impact that COVID-19 has had on nurses’ work and daily life using creative photographic data. Material and methods. This qualitative study employed a participatory action research design, and photovoice technique was used. Research data were collected from nurses working in COVID-19 clinics of various hospitals between May and September 2021. Data analysis was performed via a phenomenological interpretation method. Results. Five themes emerged from the data: (1) burnout, (2) anxiety, (3) social isolation, (4) emphasis on professional value, and (5) the value of life. Each theme was presented with representative photographic and written narratives provided by the participants. Conclusion. The findings of this study suggest that nurses experience problems such as burnout, anxiety, and social isolation. All the participants associated these problems with the negative effects of the COVID-19 pandemic on work and daily life. On the other hand, the participants emphasized professional value and the value of life despite all the negativities and risks.
Ethical approval for the study was obtained from Necmettin Erbakan University Ethics Committee for Scientific Research in Health Sciences (decision no. 2021-6 date: 2/2021).
Keywords: COVID-19; pandemic; Photovoice; nursing care; qualitative research